Representasi Kritik Sosial dan Nilai Pendidikan dalam Film Air Mata di Ujung Sajadah serta Pemanfaatannya sebagai Bahan Ajar Sastra di SMA: Representation of Social Criticism and Educational Values in the Film Air Mata di Ujung Sajadah and Its Utilization as Literature Teaching Material in Senior High School - Sopia Ananta; Hendri Henrian Algadri; Nanang Maulana (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This research is motivated by the importance of understanding moral messages and social criticism implied in modern literary works, particularly films. The purpose of this study is to describe the forms of social criticism and educational values represented in the film Air Mata di Ujung Sajadah directed by Key Mangunsong and to explain its utilization as literature teaching material in senior high schools. This study applies a qualitative approach using the semiotic analysis of Ferdinand de Saussure, which emphasizes the relationship between the signifier and the signified. The findings reveal that the film represents social criticism related to injustice, poverty, family conflict, and religious issues. In addition, the educational values reflected in the film include responsibility, care, sincerity, and the importance of maintaining family harmony. These findings are relevant to literature learning in senior high schools, particularly in film appreciation and literary analysis. The film can serve as concrete teaching material to instill moral values, develop critical thinking skills, and foster students’ empathy toward social realities within society.